Migrations, Religions and Law: The Tradition of the “Nestorian” Church of the East (5th-21st Centuries) - Cellurale, Mariateresa (2023)
Religious regimes of normativity, pertaining to non-catholic traditions of Christianity, which are particular to the history of Asia, where they originated and throve between late antiquity and early modern age, provide a powerful testimony as to social, legal and cultural entanglements that cannot be acknowledged nor understood from the binary vision of the Kulturkampf between the “East” and the “West”. Case in point: the tradition of the “Nestorian” Church of the East, with its early spread eastward, from Mesopotamia and Persia to India and China, through all of Central Asia, long before the catholic and protestant missions of the late Middle Ages and the modern age (14th to 19th centuries), defies the paradigms of postcolonial analysis. Legal and liturgical multilingual documents and monuments of the Church of the East—born from the persecution of the followers of Nestorius and Theodore of Mopsuestia under the Roman rule, established in Eastern Mesopotamia as a self-standing denomination under the katholikós, since 410—, reflect an original and autonomous Christian culture, risen from heresy, independent from any papal or imperial agenda. Its bodies of theological doctrines and liturgical formularies, particularly its legal texts, reveal a transnational, non-exclusively confessional mindset, open to hybridization. Likewise, the legal and liturgical system of the Church of the East, developed over eight centuries through migrations, commerce, missional and literary activity (writing and translations) along the Silk Roads trade and knowledge network, provided governance and justice for Christians (and also non-Christians) belonging to many peoples in diverse territories. Built with a communal rather than institutional outreach, the tradition of “Nestorian” Christianity is a genuinely “Eastern” one. It survives among us, confirmed and reinforced in its jurisdictional and pastoral structures, but also misinterpreted and misplaced, as to its role in the context of the history of Asia. Challenged and hunted, it’s facing oblivion, dispersion and, eventually, annihilation.